Re: Joyce
XVII, 282 p.
Keywords: Re: Joyce offers readers of James Joyce a significant collection of new essays from an international array of prominent and emerging Joyce scholars from around the world. Combining a wide range of theoretical approaches, this collection intervenes with current debates about Joyce's work and the place of Joyce in the academy, while addressing all principal areas of Joycean scholarship. In addition to this, the volume raises issues relevant to the study of Joyce in the context of modernism. Grouped thematically, the essays which comprise Re: Joyce offer all students of Joyce an exciting range of in-depth encounters with the pre-eminent writer of the twentieth century.